Helminth Infection Levels on Rattus rattus (Rodentia: MURIDAE) from Corrientes city, Argentina - Gómez Muñoz, María de Los Ángeles; Robles, Maria del Rosario; Milano, Alicia María Francisca; Navone, Graciela Teresa
The aim of this study was to describe the infection levels of helminths of Rattus rattus in Corrientescity, Corrientes Province, Argentina. In order to determine the role of rodents as potential reservoirsfor zoonotic parasites, different indices of helminth infection were assessed with respect to sex, age, seasonand urban landscapes. A total of 107 individuals of R. rattus were examined. Seven species of helminths werefound. The values of total prevalence, mean intensity and mean abundance were 68%, 20 and 13, respectively.Nippostrongylus brasiliensis was the species more prevalent and abundant. The results showed that the age ofthe rodents and the season of capture had effects on the helminth infection Niveles de infección de helmintos de Rattus rattus (Rodentia: Muridae) en la ciudad de Corrientes, Argentina. El objetivo del trabajo fue describir los niveles de infección de Rattus rattus en la ciudad de Corrientes, provincia de Corrientes, Argentina. Con el objetivo de determinar el rol de los roedores como reservorios potenciales de parásitos zoonóticos, se analizó la distribución de helmintos respecto al sexo, edad, estación del año y ambientes urbanos. Un total de 107 individuos de R. rattus fueron examinados. Se identificaron siete especies de helmintos. Los valores de prevalencia total, intensidad media y abundancia media fueron 68%, 20 y 13, respectivamente. Nippostrongylus brasiliensis fue la especie más prevalente y abundante. Los resultados demostraron que la edad de los roedores y la estación del año tuvieron efectos en la infección con helmintos Fil: Gómez Muñoz, María de Los Ángeles. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas, Naturales y Agrimensura. Departamento de Biología. Laboratorio Biología de los Parásitos; Argentina Fil: Robles, Maria del Rosario. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Estudios Parasitológicos y de Vectores. Universidad Nacional de La Plata. Facultad de Ciencias ...